HBV sequence integrated to enhancer acting as oncogenic driver epigenetically promotes hepatocellular carcinoma development - Lu Chen; Wenxuan Li; Wenjing Zai; Xiangyi Zheng; Xianlong Meng; Qunyan Yao; Wei Li; Ying Liang; Mu Ye; Kaicheng Zhou; Mengxing Liu; Zhicong Yang; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background HBV integration is considered as the main contributor to hepatocellular carcinoma (HCC). However, whether HBV integrated sequences determine genotype pathogenicity and how to block their function during HCC progression remains unclear. Methods An in vitro HBV-infected PHH model and liver cancer cell lines were established to confirm the pathogenic potential of HBV-SITEs. The roles of HBV-SITE-1 in HCC development were analyzed using cellular phenotypic assays and molecular biology techniques, including the combined analysis of RNA-seq and ChIP-seq. Animal models were also used to evaluate the therapeutic effect of HBV-miR-2 inhibitors. Results We identified nine fragments of HBV Sequences Integrated To Enhancer, termed as “HBV-SITEs”. Particularly, a single nucleotide variation (T > G) was embedded at seed sequence of HBV-miR-2 in the highest integrated HBV-SITE-1 between genotypes B and H. Unexpectedly, B-HBV-SITE-1, not H-HBV-SITE-1, could abnormally activate oncogenic genes including TERT and accelerate HCC cell proliferation and migration. Meanwhile, HBV-miR-2 was gradually increased in HBV-infected cells and patient plasma with different HCC stages. Importantly, 227 genes upregulated by HBV, were also activated by HBV-miR-2 through triggering HBV-SITE-1 enhancer. Conversely, enhancer activities were particularly decreased by HBV-miR-2 inhibitors, and further downregulated activated oncogenic genes. Finally, HCC growth was dramatically restrained and HBV-induced transcripts were systematically reduced via injection of HBV-miR-2 inhibitors in animal models. Conclusion HBV-SITEs were identified as novel oncogenic elements for HCC, which provides an insightful perspective for the other cancers caused by oncogenic DNA viruses. We demonstrated that the integrated HBV sequence itself acted as oncogenic enhancers and nucleotide variations of HBV genotypes account for particular pathogenic progression, supporting that the viral nucleotide sequences are vital pathogenic substances beyond viral proteins. And modulation of their enhancer activities could be clinically achievable strategy for blocking DNA viruses-related cancer progression in the future.